(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: The most typical symptom that prompts patients to visit a doctor is pain. Pain is an experience as well as a sensory modality. People’s reactions to pain might vary greatly from one another as well as from moment to moment within the same person. Aim and Objective: The present research was aimed to examine effect of Supplementation of low dose Intravenous Dexmedetomidine on characteristics of Spinal Anaesthesia with Hyperbaric Bupivacaine on motor block parameters. Methodology: The current study was conducted at Santosh Medical College & Hospital in Ghaziabad on 50 patients who were ASA l & ll and had lower abdomen and lower limb procedures. The patients’ ages ranged from 18 to 65, and their weights ranged from 30 to 70 kg for both sexes. Result: In the study’s sample, there were 32 men and 18 women. The mean age in groups D was 36.28 + 12.70 years, compared to 39.36 + 13.43 years in groups C. Mean onset time of sensory block was reported as 5.95±3.486 in group D and 7.90±3.538 in group C which was statistically significant, p=0.001 Mean VAS score in the D & C group remained zero for 90 minutes after the administration of the drug. Conclusion: Dexmedetomidine group’s sensory block onset time is earlier. The study found that Dexmedetomedine administered intravenously during spinal anesthesia decreased the onset and maximum motor blockage of sensory blocks.